2014
DOI: 10.1063/1.4893990
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular symmetry-adapted perturbation theory study of large organic complexes

Abstract: Binding energies for the complexes of the S12L database by Grimme [Chem. Eur. J. 18, 9955 (2012)] were calculated using intermolecular symmetry-adapted perturbation theory combined with a density-functional theory description of the interacting molecules. The individual interaction energy decompositions revealed no particular change in the stabilisation pattern as compared to smaller dimer systems at equilibrium structures. This demonstrates that, to some extent, the qualitative description of the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(170 citation statements)
references
References 130 publications
6
164
0
Order By: Relevance
“…Hence, interaction energies at the DLPNO-CCSD(T)/CBS level of theory have been consistently computed for L7 and S12L (Table 2). Hesselmann et al 57 showed that the deformation energies can be important for compounds of S12L and they should be taken into account to provide accurate interaction energy values. Additionally, it was proven that the deformation energies can be overestimated by MP2 due to its overbinding tendency in π-π supramolecular complexes (especially in compounds 3a and 3b).…”
Section: 23 Thementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, interaction energies at the DLPNO-CCSD(T)/CBS level of theory have been consistently computed for L7 and S12L (Table 2). Hesselmann et al 57 showed that the deformation energies can be important for compounds of S12L and they should be taken into account to provide accurate interaction energy values. Additionally, it was proven that the deformation energies can be overestimated by MP2 due to its overbinding tendency in π-π supramolecular complexes (especially in compounds 3a and 3b).…”
Section: 23 Thementioning
confidence: 99%
“…56 More recently, Hesselmann et al 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 adapted perturbation theory combined with a density-functional theory description of the interacting molecules. 57 Due to the difference in the methods employed to estimate the reference binding energies in L7…”
Section: 23 Thementioning
confidence: 99%
“…47 The adequate basis-set representation of the intermolecular space has a large impact on the calculation of noncovalent interactions in dispersion-corrected DFT, 47 as well as with other methods. 35 The calculations in ref 23 used PBE-XDM with a combination of basis sets called mixedTZ:cc-pVTZ(seg-opt) for all dimers except 7a, for which TZV was used. Both of the basis sets that form the mixedTZ set lack diffuse primitives.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…62 In sharp contrast, Hesselmann has shown in a recent study that the Symmetry-Adapted Perturbation Theory (SAPT) breakdown of the total energy for the S12L complexes does not have a signature that is particularly different from those of smaller dimers. 35 Then, what is the reason for the results shown in Table 4?…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation